Boron removal by glucamine-functionalized inverse vulcanized sulfur polymer - Abbasi, A. (Elsevier B.V., 2022)
Boron removal by novel sulfur-based boron selective adsorbent is herein reported. The sulfur-based polymer prepared by the inverse vulcanization of sulfur and 4-vinylbenzyl chloride (VBC) under optimized reaction conditions was used as a substrate and further functionalized by N-methyl-D-glucamine (NMDG) under optimized reaction conditions. Batch adsorption boron removal tests showed that a pH of 9 results in the highest adsorption capacity while an increase in the adsorbent dosage also showed a non-linear increase in the removal capacity. Acid and alkali regeneration of the used adsorbent showed 86 of its initial capacity after five cycles. The equilibrium isotherms of the adsorption were best fitted with the Redlich-Peterson model indicating that the boron adsorption obeys the principles of both monolayer and multilayer adsorption with a Langmuir maximum adsorption capacity of 7.186 mg/g. On the other hand, pseudo-second-order best fitted the adsorption kinetics meaning that chemisorption is the main controlling mechanism. The thermodynamic studies showed an endothermic spontaneous adsorption process with an increased randomness degree at the solid/liquid interface after the adsorption. The developed adsorbent is the first sulfur-rich polymer and selective boron adsorbent that can effectively reduce boron in water while also offering a considerably lower price due to utilizing the cheap and already available elemental sulfur. Â© 2022